Systematic review of musculoskeletal injuries in professional golfers. Issue 1 (10th January 2019) - Robinson, Patrick G; Murray, Iain R; Duckworth, Andrew D; Hawkes, Roger; Glover, Danny; Tilley, Nigel R; Hillman, Rob; Oliver, Christopher W; Murray, Andrew D
Abstract : Objective: The distribution of injuries affecting professional golfers is yet to be fully understood. We performed a systematic review of the clinical literature to establish the epidemiology of musculoskeletal injuries affecting professional golfers. Design: Systematic review. Data sources: Searched databases in July 2018 were PubMed, SPORTDiscus and Embase. Eligibility criteria: Published observational research articles relating to the incidence or prevalence of musculoskeletal injuries in professional golfers, which were written in the English language and not restricted by age or gender. Results: Of the 1863 studies identified on the initial search, 5 studies were found to satisfy the inclusion criteria for analysis. The mean age of the golfers in these studies was 34.8 (±3.6) years. The gender of patients in included studies compromised 72% males and 28% females. Four studies reported that lumbar spine injuries were the most common (range 22%–34%). Excluding injuries to the spine (lumbar, thoracic and cervical), the hand/wrist was the next most common region of injury (range 6%–37%). The quality of the studies was relatively poor with no study satisfying >50% of the quality assessment tool questions and only one study giving a clear definition of how they defined injury. Conclusion: There is a paucity of well-designed epidemiological studies evaluating musculoskeletal injuries affecting professional golfers. Injuries to the spine are the most frequently affected region, followed by the hand/wrist. This study has identified targeted areas of future research that aims to improve the management of injuries among professional golfers.